Antibiotic resistance in the opportunistic pathogen Stenotrophomonas maltophilia - Sánchez, María B. (Frontiers in Microbiology, 2015)
Stenotrophomonas maltophilia is an environmental bacterium found in the soil, associated with plants and animals, and in aquatic environments. It is also an opportunistic pathogen now causing an increasing number of nosocomial infections. The treatment of S. maltophilia is quite difficult given its intrinsic resistance to a number of antibiotics, and because it is able to acquire new resistances via horizontal gene transfer and mutations. Certainly, strains resistant to quinolones, cotrimoxale and/or cephalosporins - antibiotics commonly used to treat S. maltophilia infections - have emerged. The increasing number of available S. maltophilia genomes has allowed the identification and annotation of a large number of antimicrobial and heavy metal resistance genes. Most encode inactivating enzymes and efflux pumps, but information on their role in intrinsic and acquired resistance is limited. Non-typical antibiotic resistance mechanisms that also form part of the intrinsic resistome have been identified via mutant library screening. These include non-typical antibiotic resistance genes, such as bacterial metabolism genes, and non-inheritable resistant phenotypes, such as biofilm formation and persistence. Their relationships with resistance are complex and require further study.